Writing the results - Ng, K.H.; Peh, W.C.G. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
The purpose of the results section is to present the main data collected and the observations made during the research. It provides interpretation of the analysed data and does not contain details on the methods, materials or discussion. The first step in writing the results section is to review the analysed data and determine which results to present. This can be done by deciding which results are relevant to the question(s) presented in the introduction, and may be supplemented by illustrative tables and figures. The results section guides the reader through the questions investigated in the study and sets the stage for the discussion in the next section.